Real time numerical reconstruction of digitally recorded holograms in digital in-line holographic microscopy by using a graphics processing unit - Trujillo, C.; Restrepo, John F.; Garcia-Sucerquia, J. (Photonics Letters of Poland, 2010)
Digital in-line holographic microscopy (DIHM) is perhaps the simplest methodology to obtain three-dimensional information from the micrometre world. The recovery of complex amplitude scattered by the specimens, relies on quite robust algorithms that consume large amounts of time. In this letter is presented the numerical reconstruction in real-time of holograms acquired in DIHM. The use of a graphics processing unit combine with a reduced number of operations allows for reconstructing DIHM holograms of 1024x1024 pixels up to 32 frames per second. Full text: PDF References: J. Garcia-Sucerquia, W. Xu, S.K. Jericho, P. Klages, M.H. Jericho, H.J. Kreuzer, "Digital in-line holographic microscopy", Appl. Opt. Lett. 45, 836 (2006). [CrossRef] W. Xu, M.H. Jericho, H.J. Kreuzer, I.A. Meinertzhagen, "Tracking particles in four dimensions with in-line holographic microscopy", Opt. Lett. 28, 164 (2003). [CrossRef] H.J. Kreuzer, Holographic Microscope and Method of Hologram Reconstruction (US Patent 6.411.406 B1 2002). E.B. Ford, "Parallel algorithm for solving Kepler’s equation on Graphics Processing Units: Application to analysis of Doppler exoplanet searches", New Astro. 14(4), 406 (2009). [CrossRef] T. Shimobaba, Y. Sato, J. Miura, M. Takenouchi, T. Ito, "Real-time digital holographic microscopy using the graphic processing unit", Opt. Exp. 16, 11776 (2008). [CrossRef] U. Schnars, W. Juptner, "Digital recording and numerical reconstruction of holograms", Meas. Sci. Technol. 13 R85, 9 (2002). [CrossRef] M. Sypek, C. Prokopowicz, M. Gorecki, "Image multiplying and high-frequency oscillations effects in the Fresnel region light propagation simulation", Opt. Eng. 42, 3158 (2003). [CrossRef] H.J. Kreuzer, K. Nakamura, A. Wierzbicki, "Theory of the point source electron microscope", H.W. Fink, H. Schmid, Ultramicroscopy 45, 381 (1992). [CrossRef] L. Bluestein, "A linear filtering approach to the computation of discrete Fourier transform", IEEE. T on Audio and Electroacoustics. 18, 451 (1970). [CrossRef] 2006-2010 NVIDIA Corporation, CUDA Zone (2010), http://developer.download.nvidia.com/compute/cuda/3_1/ toolkit/docs/NVIDIA_CUDA_C_ProgrammingGuide_3.1.pdf J. Garcia-Sucerquia, D. C. Alvarez-Palacio, H.J. Kreuzer, "High resolution Talbot self-imaging applied to structural characterization of self-assembled monolayers of microspheres", Appl. Opt. 47, 4723 (2008). [CrossRef] K. Patorski, "The Self-Imaging Phenomenon and its Applications", Progr. Opt., E. Wolf, ed, 27, 3 (1989). [CrossRef] H.J. Kreuzer, P. Klages, A software package for the reconstruction of digital in-line and other holograms (Helix Science Applications, Halifax, N.S., Canada 2006).